Sistem Pengarsipan Dan Monitoring Surat Menyurat Di Dinas Pendidikan Gresik - Ainul Faradisa; Soffiana Agustin (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The manual archiving process within the Gresik Education Office continues to encounter significant challenges, including difficulties in correspondence tracking, document misplacement, and inefficiencies in disposition management. To address these issues, this study proposes the design and implementation of a Web-Based Archiving and Correspondence Monitoring System developed using the Waterfall methodology. The system aims to facilitate the digital transformation of administrative correspondence through three primary pillars: secure user authentication, flexible digital workflows, and compliance with electronic archival standards. Core features include centralized document management, automated disposition processes, electronic signature verification, and real-time notification integration via WhatsApp. Implementation results demonstrate that the proposed system enhances efficiency, traceability, and accountability in correspondence management at the Gresik Education Office.